British Masculinity in the Gentleman's Magazine, 1731 to 1815 - Williamson, Gillian; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The Gentleman's Magazine was the leading eighteenth-century periodical. By integrating the magazine's history, readers and contents this study shows how 'gentlemanliness' was reshaped to accommodate their social and political ambitions.
Keywords: Civilization-History.; Social history; Great Britain-History.; History, Modern; Sociology